The MERMAID study: indoor and outdoor average pollutant concentrations in 10 low-energy school buildings in France - Verriele, M.; Schoemaecker, C.; Hanoune, B.; Leclerc, N.; Germain, S.; Gaudion, V.; Locoge, N. (Indoor air, 2016)
Indoor air quality was characterized in 10 recently built energy‐efficient French schools during two periods of 4.5 days. Carbon dioxide time‐resolved measurements during occupancy clearly highlight the key role of the ventilation rate (scheduled or occupancy indexed), especially in this type of building, which was tightly sealed and equipped with a dual‐flow ventilation system to provide air refreshment. Volatile organic compounds (VOCs) and inorganic gases (ozone and NO2) were measured indoors and outdoors by passive techniques during the occupied and the unoccupied periods. Over 150 VOC species were identified. Among them, 27 species were selected for quantification, based on their occurrence. High concentrations were found for acetone, 2‐butanone, formaldehyde, toluene, and hexaldehyde. However, these concentrations are lower than those previously observed in conventional school buildings. The indoor/outdoor and unoccupied/occupied ratios are informative regarding emission sources. Except for benzene, ozone, and NO2, all the pollutants in these buildings have an indoor source. Occupancy is associated with increased levels of acetone, 2‐butanone, pentanal, butyl acetate, and alkanes.